1999
DOI: 10.1093/jnci/91.13.1138
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Ceramide and Induction of Mixed Apoptosis/Necrosis by N-(4-Hydroxyphenyl)- retinamide in Neuroblastoma Cell Lines

Abstract: 4-HPR may form the basis for a novel, p53-independent chemotherapy that operates through increased intracellular levels of ceramide and that retains cytotoxicity under reduced oxygen conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
217
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(230 citation statements)
references
References 58 publications
9
217
2
2
Order By: Relevance
“…Previously, Radin has reported that the inhibition of GCS with PDMP, a glucosylceramide analog, results in an increase in the levels of ceramide and sphingosine and also a decrease in protein kinase C levels in mouse Ehrlich ascites carcinoma cells and in rat glioma cells, that is, GCS inhibition enhances the anti-proliferative effects of chemotherapeutics on cancer cells [71,72]. Maurer et al [73] have also reported that GCS inhibition increases the intracellular ceramide levels and enhances the cytotoxic effects of 4-HPR and safingol in tumor cells. Not only in vitro but also in vivo studies have shown that progression of melanoma cells decreases in response to GCS suppression, and thus P-gp inhibition [74,75].…”
Section: Glucosylceramide Synthase In Cancer Therapymentioning
confidence: 99%
“…Previously, Radin has reported that the inhibition of GCS with PDMP, a glucosylceramide analog, results in an increase in the levels of ceramide and sphingosine and also a decrease in protein kinase C levels in mouse Ehrlich ascites carcinoma cells and in rat glioma cells, that is, GCS inhibition enhances the anti-proliferative effects of chemotherapeutics on cancer cells [71,72]. Maurer et al [73] have also reported that GCS inhibition increases the intracellular ceramide levels and enhances the cytotoxic effects of 4-HPR and safingol in tumor cells. Not only in vitro but also in vivo studies have shown that progression of melanoma cells decreases in response to GCS suppression, and thus P-gp inhibition [74,75].…”
Section: Glucosylceramide Synthase In Cancer Therapymentioning
confidence: 99%
“…Accordingly, while apoptosis by HPR appears receptor-independent (Delia et al, 1993;Kitareewan et al, 1999), and actually correlates with the ability of HPR to elicit intracellular free radicals and acidi®cation (Delia et al, 1997a;Angoli et al, 1996;Maurer et al, 1999;Suzuki et al, 1999), transcriptional regulation of target genes (e.g. AP1) is retinoid-receptor dependent, according to data showing that HPR selectively activates the transcription by RAR-g, to a less extent by RAR-b, but not by RAR-a (Fanjul et al, 1996;Kazmi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting a role for ceramide during 4HPR action on HL-60 leukaemia cells and neuroblastoma cells is based on studies demonstrating an elevation of cellular ceramide levels in response to 4HPR and the ability of the ceramide synthase inhibitor fumonisin B 1 (FB 1 ) to block this ceramide response and prevent 4HPR-induced apoptosis (DiPietrantonio et al, 1998;Maurer et al, 1999). However, in other instances where induction of apoptosis is accompanied by an elevation of ceramide, FB 1 failed to prevent the apoptotic response while blocking ceramide production (Nagy et al, 2000;Miguet et al, 2001).…”
mentioning
confidence: 99%